Experimental investigation on cyclic response of RC elements repaired by CFRP external reinforcing systems. (1st March 2017) - Capani, Francesco; D'Ambrisi, Angelo; De Stefano, Mario; Focacci, Francesco; Luciano, Raimondo; Nudo, Raffaele; Penna, Rosa
Abstract: This paper deals with the experimental results of an investigation aimed at studying cyclic response of half scaled RC specimens previously damaged and then repaired with externally bonded carbon fiber reinforced polymer sheets. The research involved the test of ten specimens. Two of them were tested without any external strengthening material in order to provide a reference for the response of repaired specimens. These latter were tested after a previous damaging procedure and a subsequent repair intervention with fiber reinforced polymer composites. The parameters under investigation were the level of initial damage, the strengthening configuration, and the level of axial load. Test results have pointed out effectiveness of the adopted strengthening systems, since repaired specimens exhibited better mechanical responses than the unstrengthened ones.